First love II - Soh, Francesca Magdalene Min Hwei (Nanyang Technological University, 2022)
A Final Year Project Essay on First Love II. Project speaks about the artist's personal journey to motherhood which deeply stems from her own mother child relationship. The essay will speak about her background, developments, processes and her closure.